Formulaic language: translation strategies of Malay sayings and proverbs in the film Magika (2010) - Roslan, Azamuddin; Mohd Noor, Maizura (Universiti Teknologi MARA, 2023)
This study examines the linguistic and cultural translation of a Malay film, focusing on a subset of formulaic language, namely sayings and proverbs. It employs a qualitative approach, specifically utilizing the content analysis method, to thoroughly compare the film's dialogues with the accompanying English subtitles, with a specific emphasis on the translator's choices in this translation process. The results reveal that the communicative intent of the identified sayings and proverbs in the film is generally well-preserved and transferred into the English subtitles. While there are similar expressions in the target language, the translator often opted for the literal translation of the Malay sayings and proverbs to capture the characters' conversational styles and context. The analysis highlights the importance of translators’ proficiency in both source and target languages as well as cultural competence in both communities.